Reactogenicity and Immunogenicity of the Pfizer and AstraZeneca COVID-19 Vaccines - Mahallawi, Waleed H.; Mumena, Walaa A. (Frontiers in Immunology, 2021)
Background The relationships of the coronavirus disease 2019 (COVID-19) vaccination with reactogenicity and the humoral immune response are important to study. The current study aimed to assess the reactogenicity and immunogenicity of the Pfizer and AstraZeneca COVID-19 vaccines among adults in Madinah, Saudi Arabia. Methods A cross-sectional study, including 365 randomly selected adult Pfizer or AstraZeneca vaccine recipients who received a homologous prime-boost vaccination between February 1st and June 30th, 2021. Data of height and weight were collected to assess the weight status of percipients. An evaluation of seropositivity for anti-severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) antibodies was assessed using enzyme-linked immunosorbent assay (ELISA). Results Among the participants, 69% (n = 250) reported at least one vaccine-related symptom. Pain at the injection site was the most frequently reported vaccine-related symptom. The mean total score for vaccine-related symptoms was significantly higher among participants who received the AstraZeneca vaccine, women, and participants with no previous COVID-19 infection (p < 0.05). Spike-specific IgG antibodies were detected in 98.9% of participants after the receipt of two vaccine doses, including 99.5% of Pfizer vaccine recipients and 98.3% of AstraZeneca vaccine recipients. Significantly, higher proportions of participants in the <35-year age group developed a humoral immune response after the first vaccine dose compared with the participants in other age groups. Conclusion Participants who received the Pfizer COVID-19 vaccine reported fewer vaccine-related complications compared with those who received the AstraZeneca COVID-19 vaccine, but no serious side effects were reported in response to either vaccine. Health status and age were factors that may influence COVID-19 vaccine effectiveness for the generation of antibodies against the SARS-CoV-2 spike protein.